RANCANG BANGUN E- COMMERCE TOKO RAFFAMART PALEMBANG MENGGUNAKAN MACROMEDIA DREAMWEAVER - Muhammad Nasir; Imam Solikin (Jurnal Ilmiah Matrik, 2018)
Raffamart Store is one of the trading business that sells various clothes. This store has not provided product sales service via internet or e-commerce (Electronic Commerce). In the process of selling ordering products as well as transactions, customers must come directly to the store. Customers can not place product orders due to system limitations owned by Raffamart stores. Therefore, a web-based sales system (e-commerce) is needed to assist the store in promoting the product. System development method used is waterfall method. The tools used to illustrate the system model are use case diagrams, activity diagrams and class diagrams. This website was developed using macromedia dreamweaver, programming language PHP and MySQL as database. With this web-based system, of course, will facilitate the processing of product data for sale and also help in terms of product marketing, because any information provided to customers can be faster.